Severe Fading And Outdated Channel Condition Models In Relay Communication Networks - Zakaria, Jamaluddin (2019)
Cooperative communication system is an attractive method which enhances the performance diversity by introducing an intermediate relay for assisting the primary communication between the source and the destination terminals. There are two main issues regarding to the communication channel. The first one is the severe fading channel where the analysis is performed mainly for investigating the direct source-todestination (SD) link in wireless cooperative network. Most of the works omits SD link by simply assuming deep fade with no consideration of partial contribution to the overall system diversity. This is due to the imprecise classification of Rayleigh fading as severe fading. The second issue is a relative movement in communication terminals cause some delay in propagating the transmitted signals which is subject to the established Jakes’ autocorrelation model. This is also known as outdated channel condition. It causes the destination terminal unable to estimate or recover the source’s information properly that will deteriorate the system performances. For the first issue, the analytical expressions based on this severe fading channel model has come to an approach of utilizing the moment generating function (MGF). The MGF expression of the Weibull distribution model has to deal with a complex Meijer’s G-function and due to the complexity and limitation in the existing MGF expression, it is scarce to have performance analysis based on the expression. To overcome this limitation, infinite series of MGF expression for the Weibull model is proposed. This expression is then, utilized for evaluating the impact of severe fading channel on the direct SD link in a three-terminal cooperative network by employing approximated variablegain and fixed-gain amplify-and-forward (AF) relaying schemes associates with the maximal ratio combining (MRC) and the selection combining (SC) schemes. Under predefined parameters setting, it is found that when the direct SD link is in deep fade, the diversity gain for both MRC and SC for AF variable-gain relaying system is 0.771. While the SD link behaves as Rayleigh channel then diversity gain is given by; MRC:1.660, SC:1.602. The second issue is investigated in a three-terminal wireless energy harvesting-based AF dual-hop cooperative system along with the assumption of dynamic terminals’ movement where it is assumed that the relay terminal is energyconstrained. New time-switching relaying protocol which considers the amount of propagation delay due to the terminal’s movement is proposed. Then, two different types of transmission mode are considered; delay-limited, DL (requires outage probability evaluation) and delay-tolerant, DT (requires ergodic capacity evaluation). It is found that when all the terminals are in static, the system achieves the maximum throughput (DL: 0.83 bit/sec/Hz, and DT: 1.59 bit/sec/Hz).